First Mate Mr. Hayward and crew members in front of covered whaleboat, west coast of Hudson Bay, Canada - Comer, George (Creator) (Ownership Statement: Mystic Seaport, 1897)
Six men stand stand in front of a covered whaleboat. They are identified as first mate Mr. Hayward and his boat crew, members of the crew of the whaling schooner Era or A.T. Gifford. Infrastructure Livelihood Title supplied by cataloger. On mount, 5 1/2 x 6 1/2 in. Photo would have been taken in the spring, during the season of floe whaling. During this time of year the whaling schooner was still frozen into the harbor ice, so the whaleboats were hauled out to the floe edge [the edge of the land-fast ice] and launched in search of whales. The boats were also provided with covers and used for shelter, as seen in this image. Taken by Captain George Comer (1858-1937), a sealer and whaling captain from East Haddam. He went to sea while still in his teens and was later master of vessels from both New London and New Bedford. Comer participated in voyages involved in polar expeditions and was noted for his studies of Arctic peoples and their environment. This photograph was taken during one of his voyages on the Era or A.T. Gifford.